OPEN BORDERS WITH UNCOORDINATED PUBLIC TRANSPORT: THE CASE OF THE SLOVENIAN-ITALIAN BORDER - Matej GABROVEC (European Journal of Geography)
Within the programme of cross-border cooperation between Slovenia and Italy, a project called TRADOMO was proposed and approved. Its aim is to improve sustainable access and mobility in the cross-border programme area. Within the framework of this project, we prepared a study on public transport proposing the steps, based on an analysis of the current situation, to improve the system of transport connections in public transport with regard to the needs of the passengers in the cross-border area. The study was made in the towns of Gorizia/Gorica and Muggia/Milje close by the Slovenian-Italian border. With the state border drawn after the Second World War these two towns were cut off from their hinterlands. Proceeding from the analyses of the revitalized traffic flows, we propose a new common organization of public transport in which municipalities on both sides of the state border would participate.